Tyrosinase‐catalyzed oxidation of resveratrol produces a highly reactive ortho‐quinone: Implications for melanocyte toxicity. (10th July 2019) - Ito, Shosuke; Fujiki, Yui; Matsui, Nina; Ojika, Makoto; Wakamatsu, Kazumasa
Abstract: trans ‐Resveratrol (3, 5, 4′‐trihydroxy‐ trans ‐stilbene, RES), a naturally occurring polyphenol, has recently attracted increased interest as a health‐beneficial agent. However, based on its p ‐substituted phenol structure, RES is expected to be a substrate for tyrosinase and to produce a toxic o ‐quinone metabolite. The results of this study demonstrate that the oxidation of RES by tyrosinase produces 4‐(3′, 5′‐dihydroxy ‐trans ‐styrenyl)‐1, 2‐benzoquinone (RES‐quinone), which decays rapidly to an oligomeric product (RES‐oligomer). RES‐quinone was identified after reduction to its corresponding catechol, known as piceatannol. RES‐quinone reacts with N ‐acetylcysteine, a small thiol, to form a diadduct and a triadduct, which were identified by NMR and MS analyses. The production of a triadduct is not common for o ‐quinones, suggesting a high reactivity of RES‐quinone. RES‐quinone also binds to bovine serum albumin through its cysteine residue. RES‐oligomer can oxidize GSH to GSSG, indicating its pro‐oxidant activity. These results suggest that RES could be cytotoxic to melanocytes due to the binding of RES‐quinone to thiol proteins.